Comparison of taurolidine with 4% ethylenediaminetetraacetic acid on antimicrobial lock effectiveness: An experimental study - Visek, Jakub; Ryskova, Lenka; Cesakova, Petra; Stanclova, Jana; Vajrychova, Marie; Blaha, Vladimir (JPEN. Journal of parenteral and enteral nutrition, 2025)
BACKGROUND: Antimicrobial lock therapy is recommended for preventing and treating catheter-related bloodstream infections, but different solutions have uncertain efficacy. METHODS: Two locks, 1.35% taurolidine and 4% ethylenediaminetetraacetic acid (EDTA), were tested on Staphylococcus epidermidis, Staphylococcus aureus, methicillin-resistant S. aureus, Pseudomonas aeruginosa, multidrug-resistant P. aeruginosa, vancomycin-resistant Enterococcus faecium, Klebsiella oxytoca (carbapenemase producing), K. pneumoniae (extended-spectrum β-lactamase producing), Candida albicans, and Candida glabrata. Broviac catheter segments were incubated with these organisms and then exposed to various lock solutions. Colony-forming units (CFUs) were counted after 2, 4, and 24 h of incubation. RESULTS: Taurolidine showed a significant decrease in CFUs after 2 h in S. aureus, S. epidermidis, methicillin-resistant S. aureus, vancomycin-resistant E. faecium, P. aeruginosa (both sensitive and multidrug-resistant strains), K. oxytoca, C. albicans, and C. glabrata. After 4 h, significant reductions were noted in S. aureus, S. epidermidis, methicillin-resistant S. aureus, P. aeruginosa, multidrug-resistant P. aeruginosa, K. pneumoniae, K. oxytoca, and C. albicans. Taurolidine was also effective after 24 h, especially against methicillin-resistant S. aureus and multidrug-resistant P. aeruginosa. Four percent EDTA acid showed a significant reduction in CFUs after 2 h in S. aureus, vancomycin-resistant E. faecium, P. aeruginosa, K. oxytoca, C. albicans, and C. glabrata. After 4 h, reductions occurred in P. aeruginosa, multidrug-resistant P. aeruginosa, K. oxytoca, and C. albicans and after 24 h in methicillin-resistant S. aureus, P. aeruginosa, and K. oxytoca. CONCLUSION: Taurolidine is more effective than 4% EDTA acid in eradicating Gram-positive and Gram-negative microorganisms and fungi.
Keywords: katétrové infekce; Colony Count, Microbial; Staphylococcus aureus; Staphylococcus epidermidis; Candida albicans; Microbial Sensitivity Tests; počet mikrobiálních kolonií; Anti-Infective Agents; taurin; Taurine; lidé; Pseudomonas aeruginosa; Methicillin-Resistant Staphylococcus aureus; Catheter-Related Infections; Edetic Acid; Humans; mikrobiální testy citlivosti; Thiadiazines; antiinfekční látky; thiadiaziny; methicilin rezistentní Staphylococcus aureus; EDTA